THERMAL-HYDROLOGIC MECHANISM FOR RAINFALL-TRIGGERED COLLAPSE OF LAVA DOMES - Elsworth D.; Voight B.; Young S.R.; Thompson G. (My University, 2004)
Hazardous gravitational collapses involving hot lava domes can be triggered by intense rainfall, both in periods of active dome growth and volcanic repose. The collapses can evolve into energetic failures involving as much as 90% of the dome, or .100 3 10 6 m 3 of dome lava, retrogressively removed over several hours. Under- standing such potentially lethal phenomena is vital, but traditional explanations for rain-induced slope failure are problematic for rainfall on hot (typically .400 8C) crystalline lava. In this paper we quantitatively develop a new thermal-hydrologic mechanism that can cause such failures: pressure buildup within fissures due to effusive gas trapped by a rain-saturated dome carapace results in increased destabilizing forces and the loss of mass strength, and ultimately results in failure of the dome. Our mechanistic models are consistent with field observations and provide a quantification of threshold rainfall intensities and durations required to trigger failure.
Keywords: lava dome; rainfall; instability; pyroclastic flows; hazard